Derivation of Adjectives from Proper Names - Kocijan, Kristina (Array, 2013)
Croatian language distinguishes three types of adjectives according to their meaning: qualitative, material and possesive adjectives. The possessive types of adjectives are further devided in two subtypes first of which answears the question 'which' or belonging to whom (bratova kuća – brother's house) while the second one answears the question 'which kind' and resembles more to qualitative adjectives (bratska ljubav – brotherly love). In this paper, authors are mainly interested in the first type of possessive adjectives, especially when they describe something belonging to a proper noun (first name, last name, geographical names, etc.). Since Croatian dictionary of proper names in NooJ has over 41 000 entries, it would be quite time, as well as space, consuming to build a possessive adjectives dictionary for all those nouns. Thus, we have decided to find the patterns for derivation of such adjectives directly from a noun it describes: • First names: Marko -> Markov, Ana -> Anina • Last names: Matoš -> Matošev • Geographical names: Zagreb -> Zagrebački, Split -> Splitski Building grammars for recognition of this type of possessive adjectives is important since it should raise the recall for both NP and PP chunks in processing Croatian texts.